Atelier Luxembourg : The Venice Biennale Projects : 1988-2011. - Lunghi, Enrico; Mudam, Luxembourg (Luxembourg : Mudam, 2012)
Lippert, Patricia ; Ney, Moritz ; Feiereisen, Marie-Paule ; Biwer, Jean-Marie ; Ney, Bertrand ; Theis, Bert ; Wolff, Luc ; Decker, Simone ; Drescher, Doris ; Tse, Su-Mei ; Prum, Antoine ; Mercedes, Jill ; Bouschet, Gast ; Hilbert, Nadine ; Feipel, Martine ; Bechameil, Jean
Atelier Luxembourg. The Venice Biennale Projects 1988-2011, Mudam, Luxembourg, 13.10.2012 - 24.02.2013
boek